2021
DOI: 10.3390/antiox10020331
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Modified LDL Suppresses Lymphangiogenesis via CD36 Signaling

Abstract: Arterial accumulation of plasma-derived LDL and its subsequent oxidation contributes to atherosclerosis. Lymphatic vessel (LV)-mediated removal of arterial cholesterol has been shown to reduce atherosclerotic lesion formation. However, the precise mechanisms that regulate LV density and function in atherosclerotic vessels remain to be identified. The aim of this study was to investigate the role of native LDL (nLDL) and oxidized LDL (oxLDL) in modulating lymphangiogenesis and underlying molecular mechanisms. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…However, manipulating VEGFR-3/VEGF-C signaling did not affect atherosclerotic plaque size and plasma cholesterol level. Oxidized LDL may also alter the growth of adventitial lymphatic vessels during atherosclerosis by acting on lymphatic endothelial cells through a CD36-dependent mechanism [93].…”
Section: Morphological and Density Alterations In Lymphatic Vessels During Atherosclerosismentioning
confidence: 99%
“…However, manipulating VEGFR-3/VEGF-C signaling did not affect atherosclerotic plaque size and plasma cholesterol level. Oxidized LDL may also alter the growth of adventitial lymphatic vessels during atherosclerosis by acting on lymphatic endothelial cells through a CD36-dependent mechanism [93].…”
Section: Morphological and Density Alterations In Lymphatic Vessels During Atherosclerosismentioning
confidence: 99%
“…Lymphatic vessels mediate the removal of oxidized LDL, thus reducing atherosclerotic lesion formation. Human lymphatic-derived endothelial cells exposed to oxidized LDL exhibit reduced angiogenic activity in vitro and neovessel formation in vivo via CD36 receptor–mediated signaling ( 109 ). Whether this signaling axis may be exploited for therapeutic benefit in atherosclerotic patients would be an advantageous line of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of oxidized lipids operated by the lymphatic vessels seems to play a significant anti-atherogenic role, although the precise mechanism remains to be identified. A very recent study demonstrated that, in human atherosclerotic arteries, oxLDLs especially accumulate in the adventitial layer, which is particularly rich in lymphatic vessels [ 139 ]. Treatment of human lymphatic endothelial cells with oxLDLs inhibited the in vitro tube formation, an effect that was prevented by siRNA-mediated knockdown of CD36 [ 139 ].…”
Section: The Oxldl Signalingmentioning
confidence: 99%
“…A very recent study demonstrated that, in human atherosclerotic arteries, oxLDLs especially accumulate in the adventitial layer, which is particularly rich in lymphatic vessels [ 139 ]. Treatment of human lymphatic endothelial cells with oxLDLs inhibited the in vitro tube formation, an effect that was prevented by siRNA-mediated knockdown of CD36 [ 139 ].…”
Section: The Oxldl Signalingmentioning
confidence: 99%